Peran Serta Manager Pelayanan Pasien (MPP) Dengan Tingkat Kepuasan Perawat Di IPIT RSUD Dr. Saiful Anwar Malang - Nurhayati, Dwi (Jurnal Keperawatan Muhammadiyah, 2024)
Organizational hospitals with complex and adaptive systems. The resulting products involve diverse, interconnected and sustainable inputs, processes and ecosystems. The expert panel study agreed on a Patient Service Manager (MPP) nursing model as an effort that is able to realize the patient's preferences or rights to determine treatment options according to their needs and expectations. This study aims to analyze the relationship between the role of the Patient Service Manager (MPP) and the level of satisfaction of nurses in providing care services at the Integrated Infection Services Installation at RSUD dr. Saiful Anwar Malang. The research method used is correlational research with a cross sectional approach. The sample in this study was 40 nurses with a sampling technique using non-probability sampling, a purposive sampling approach. The results of the research showed that the majority of respondents, namely 27 people (67,5%) nurses, stated that they were satisfied with the participation of the Patient Service Manager (MPP) in providing nursing services at the Integrated Infection Services Installation at RSUD dr. Saiful Anwar Malang and MPP participation showed that the majority of 27 respondents (67,5%) mentioned MPP participation in the category sometimes. The results of the Spearmans rho analysis test show a significant p-value of 0,000 (p<0,05, which means there is a relationship between MPP participation and the level of nurse satisfaction, with a correlation level of 0,762 which is positive/in the same direction as the level of strong correlation. The more frequently the MPP participates, the higher the satisfaction nurses. The role of MPP in resolving problems that are managed by MPP can be known early, so that nurses do not receive additional tasks and focus more on service. The role of MPP can increase cooperation, coordinate so that information errors, information delays, service do not occur.